Carga de doenças bucais crônicas: Fatores de risco associados ao agrupamento da cárie e periodontite em diferentes fases da vida - COSTA , Susilena Arouche (2022)
Introduction: Caries and periodontitis are important global public health problems, whose prevalence has remained steady over the last thirty years. In 2018, our group observed a strong correlation between caries and periodontitis indicators in Brazilian adolescents (17-18 years) and children (3-5 years), forming a latent variable called Chronic Oral Diseases Burden. Low socioeconomic status, high consumption of added sugar, obesity and high levels of IL-6 were associated with the Chronic Oral Diseases Burden in adolescents. Considering these facts, this thesis had the following objectives: 1- to investigate the Oral Diseases Burden in another population, i.e., to investigate if there is a grouping of caries and periodontitis indicators throughout the life cycle in the American population; 2- to investigate if low socioeconomic status, behavioral risk factors and obesity are associated with Oral Diseases Burden in the American population and, 3- to investigate pathways of micronutrient intake and serum levels of vitamin D, calcium and phosphorus to reduce the Oral Diseases Burden. Methods: Data from NHANES III (1988-1994) were analyzed. The constructs underlying the variables bleeding on probing (BoP), moderate probing pocket depth (PPD) (4-5mm), severe PPD (≥6mm), moderate clinical attachment loss (CAL) (3-4mm), severe CAL (≥ 5mm), furcation involvement, decayed teeth, teeth with pulpal involvement and missing teeth were deduced by Exploratory Factor Analysis in different age groups. NHANES 2011-2014 was used for sensitivity analysis. Then, using Structural Equation Modeling, we analyzed which factors (socioeconomic status, tobacco consumption, alcohol consumption, unhealthy diet, healthy diet, and obesity) were associated with these constructs. In addition, we also analyzed pathways between micronutrient intake and serum vitamin D, calcium, and phosphorus levels for the Oral Diseases Burden. All analyzes were performed using the Mplus software (version 8.0). Results: Two constructs were extracted. The first, Oral Diseases Burden, grouped caries indicators with moderate PPD and moderate CAL for the youngest (13 to 39 years old); while for individuals over 50 years, Oral Diseases Burden grouped caries indicators with severe PPD and CAL and furcation involvement. Low Socioeconomic Status and smoking increased the Oral Diseases Burden, while Healthy Diet reduced it across all age groups. Micronutrient intake and serum vitamin D levels were associated with a lower Oral Diseases Burden. Conclusion: Caries and periodontitis indicators grouped consistently across different age groups and over different time periods in the US population. A transdisciplinary approach to tackle caries and periodontitis is extremely relevant, addressing social and economic determinants, in addition to behavioral and nutritional risk factors.